4.3 EPICure 2: Impact of antenatal steroid, tocolysis and caesarean delivery on condition at birth in extremely preterm babies. (9th June 2014) - Morgan, AS; Draper, ES; Bennett, CJ; Alfirevic, Z; Costeloe, KL; Marlow, N
Abstract : Objective: To evaluate the relationship of steroid, tocolysis and caesarean delivery to the chances of the baby being born with a heart rate >100 at 5 min after birth ("good condition") and of death in labour or the delivery room ("perinatal death"). Design: Prospective cohort of all singleton births in England in 2006 at 22–26 weeks of gestation where the fetus was alive at the start of labour monitoring or decision to perform caesarean section (n = 1722). Odds ratios of outcomes were adjusted for factors including gestational age (GA) and sex (aOR). Results: Rates of intervention increased with GA (Table ). Antenatal steroid was associated with both improved condition at birth (aOR full course 1.82 (95% CI: 1.22–2.71); aOR partial course 1.38 (0.93–2.03)) and perinatal death (aOR full course 0.47 (0.31–0.74); partial course 0.37 (0.23–0.58)). Delivery route modified this association: in those delivered by caesarean section, steroid did not improve outcomes. Tocolysis was associated with improved outcomes after adjustment (aOR 1.45 (1.05–2.00) for condition at birth and 0.48 (0.32–0.73) for perinatal death). Caesarean delivery was only associated with improved outcomes at <25 weeks in 19 women not in labour. Conclusions: Babies exposed to antenatal steroid and tocolysis at extremely low gestations have improved immediate outcomes after delivery.